AMBULATORY BLOOD PRESSURE MONITORING AFTER ONE CARDIOVASCULAR EVENT IN PREDICTION OF A SECOND CARDIOVASCULAR EVENT. (June 2018) - Neves, C.; Bastos, J. Mesquita; Pires, J. Ricardo; Polónia, J.
Abstract : Objective: In patients with previous cardiovascular (CV) event it is not clear whether Ambulatory Blood Pressure Monitoring 24 H (ABPM) has prognostic value for recurrence. The objective was to compare ABPM values after a first CV event between patients with (2EV) and without (1EV) a second CV event and to evaluate if ABPM has a role in secondary prediction. Design and method: We studied 187 hypertensive patients with ABPM after a first CV event. ABPM data in 2EV vs 1EV were compared. Results: Of the 187 patients (74.3 % male) ageing 66, 6 ± 10.7 years, followed for 2.3 ± 1.9 years, 158 were 1EV and 29 were 2EV. In the 2EV, mean age was 67.2 ± 9.5 and 72.4% were male. Comparison of the ABPM parameters between the 2EV vs 1EV showed: 24H systolic blood pressure (SBP) (134 ± 15 vs 125 ± 13 mmHg, p 0.002), day SBP (138 ± 15 vs 129 ± 13 mmHg, p 0.002), night SBP (128 ± 18 vs 118 ± 16 mmHg, p 0.003), 24H pulse pressure (PP) (62 ± 13 vs 55 ± 13 mmHg, p 0.004), day PP (63 ± 13 vs 55 ± 14 mmHg, p 0.005) and night PP (62 ± 14 vs 53 ± 14 mmHg, p = 0.003). The Cox model, adjusted for gender and age, showed correlation with recurrent events for: 24H SBP (HR = 1.032, 95CI 1.005–1.060, p 0.021), day SBP (HR = 1.026, 95CI 1.001–1.052, p 0.043), night SBP (HR = 1.031, 95CI 1.007–1.055, p 0.011) and 24H PP (HR = 1.046, 95CI 1.013–1.081, p 0.007). In the survival analysis, the 24H SBP ROC curve showed an AUC of 0.627 (p 0.003). The value of 124 mmHg was the best cutoff of SBP (sensitivity 82.7, specificity 51.2) for prediction of secondary CV events. The survival Kaplan Meyer curve showed a worse prognosis for the 2EV with 24H SBP > 124 mmHg (log rank 6.032, p 0.014) (not observed in the 135 mmHg 24H SBP Kaplan Meyer, p 0.224). Conclusions: In patients with previous cardiovascular events, higher values of 24H, daytime and night-time SBP are more predictive of cardiovascular events. In our 2EV population, a 24H SBP higher than 124 mmHg is more predictive of secondary events.